Case Study - Alföldvíz, Hungary - Kis, Andras Lajos; Salvetti, Maria (World Bank, Washington, DC, 2017)
The Water Global Practice, under the WSS GSG Utility Turnaround thematic area, has implemented the Global Study on WSS Utility Aggregation to provide evidence-based guidance to policy makers and practitioners regarding when, why, and how water and sanitation utilities can work together ("aggregate") to successfully deliver specific policy outcomes, such as better services or lower costs. This work builds on a review of existing literature and an analysis of both qualitative and quantitative evidence, a global data set of international trends, a utility performance database, and a series of case studies. The deep-dive of 14 case studies of aggregation processes in seven countries (Brazil, Colombia, Hungary, Indonesia, Portugal, Mozambique, Romania) allowed conducting a qualitative analysis, by centering on the stakeholders involved, the decisions made, the roles of sector actors and their incentives, and the perceived outcomes with a view to bringing forward the essence of each case experience. The selection of the countries and specific providers was done in a manner to ensure a diversity of geography, development level, size, and aggregation design.